ANALISIS KELAYAKAN USAHA SARANG BURUNG WALET (Collocalia fuchiphaga) DI KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Beddu, Farawansyah Akbar; -, Irmayani; Malik, Andi Adam (Jurnal Ilmiah Ecosystem, 2019)
The study aimed how much the income of swallows nest in the district Maritengngae regency Sidenreng Rappang. The researcher used method of Sampling jenuh (sensus). This study was conducted in the district Maritengngae regency Sidenreng Rappang and using sampling 50 enterpeuners swallows nest. This study concist 3 group, little scale, average scale, and large scale. Study use analysis finansial Net Present Value, Net Benefit Cost Ratio, Gross Benefit Cost Ratio, Internal Rate of Return, and Payback Period. The result showed enterpeuner swallows nest little scale have income Rp20.000.00,00/year and the discount factor 6% NPV Rp48.454.578,00, Net B/C 2,29%, Gross B/C 1,60%, IRR 30,80% and PBP 2,96 the return of finansial during 2 years 9 month 6 days. The result showed enterpeuner swallows nest average scale have income Rp50.000.00,00/year and the discount factor 6% NPV Rp339.474.104,00, Net B/C 3%, Gross B/C 2,09%, IRR 29,93% and PBP 3,33 the return of finansial during 3 years 3 month 3 days. The result showed enterpeuner swallows nest large scale have income Rp120.000.00,00/year and the discount factor 6% NPV Rp940.852.808,00, Net B/C 3%, Gross B/C 2,09%, IRR 30,67% and PBP 3,26 the return of finansial during 3 years 2 month 6 days. Based on the study, the enterpeuner of swallows nest in the district Maritengngae regency Sidenreng Rappang feasible to developed because a provides economic benefits.